Impact of Booroola fecundity gene introgression on sheep production: Indian perspective - KUMAR, ARUN; KUMAR, RAJIV; MISRA, S S; SHARMA, R C (The Indian Journal of Animal Sciences, 2021)
Surge of demand for meat from diverse sources in a time of decling land and other natural resources shifted the trend of producing more sheep per sheep. Prolificacy aspect in sheep can be used as an important arsenal to fulfil this objective. FecB gene mutation perhaps spread from Garole microsheep of India, has been widely used for introduction of prolificacy in monotocus sheep worldwide. The ovulation rate and litter size are two most important reproductive parameters influenced by FecB gene besides small influences on other sheep production parameters. While implementing the FecB introgression programmes precaution needs to be observed to avoid lamb mortality. The results of the experiments conducted worldwide on FecB introgression programmes suggest that high prolificacy is economically beneficial under intensive and semi-intensive management system of sheep rearing. There were variable effects of FecB genotype documented from different parts of the world. With goal oriented research efforts, the prolificacy in FecB carrier Avishaan sheep, a triple breed cross developed from Garole, Malpura and Patanwadi at ICAR-CSWRI are showing promising sheep for future. There are several challenges for using FecB gene in the future using assisted reproductive and genome editing technology. The effect of FecB gene on different sheep production parameters as reported in the literature are summarized in present work.